Comparative Study of Antifungal Activities of Six Selected Essential Oils against Fungal Isolates from Cheese Wagashi in Benin - SESSOU, PHILIPPE; FAROUGOU, SOUAÏBOU; AHOUNOU, G. SERGE; YEDOMONHAN, HOUNNANKPON; AZOKPOTA, PAULIN; YOUSSA, ALASSANE; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2013)
The study has compared the antifungal efficacy of six essential oils, Cinnamomum zeylanicum, Cymbopogon citratus, Ocimum gratissimum, Pimenta racemosa, Syzygium aromaticum and Zingiber officinale, tested in culture medium and in traditional cheese wagashi system against moulds belonging to Aspergillus, Penicillium, Fusarium and Scopulariopsis genera in perspective to select the most actives as substitutes of chemical preservatives for wagashi preservation. Results obtained from this work indicated that Syzygium aromaticum, Pimenta racemosa, Ocimum gratissimum and Cymbopogon citratus essentials oils were the most actives extracts at in vitro assay in decreasing order with strong fungistatic activity against the isolates tested; the pronounced activity was provided by S. aromaticum essential oil. The effectiveness of these actives oils on the less sensitive moulds common to these oils showed that, among these extracts that of Syzygium aromaticum in particular exerted high sporale reduction against all the strains tested. In sum, Syzygium aromaticum essential oil possessed the highest antifungal activity both in culture medium and in wagashi system. Essential oils of C. citratus, O. gratissimum, P. racemosa and above all that of S. aromaticum, among the six extracts investigated, were the most promising oils as wagashi additives in substitution of synthetic chemicals ones to extend shelf life time of this by-product of milk for its valorization. Further studies are needed to be performed on the safety of oils for human, the shelf life time of this cheese and its acceptability when treated with essential oils to reduce and control pathogen contamination or native microflora
Keywords: wagashi